Chloroform‐Assisted Rapid Growth of Vertical Graphene Array and Its Application in Thermal Interface Materials. Issue 15 (24th March 2022) - Xu, Shichen; Cheng, Ting; Yan, Qingwei; Shen, Chao; Yu, Yue; Lin, Cheng‐Te; Ding, Feng; Zhang, Jin
Abstract: With the continuous progress in electronic devices, thermal interface materials (TIMs) are urgently needed for the fabrication of integrated circuits with high reliability and performance. Graphene as a wonderful additive is often added into polymer to build composite TIMs. However, owing to the lack of a specific design of the graphene skeleton, thermal conductivity of graphene‐based composite TIMs is not significantly improved. Here a chloroform‐assisted method for rapid growth of vertical graphene (VG) arrays in electric field‐assisted plasma enhanced chemical vapor deposition (PECVD) system is reported. Under the optimum intensity and direction of electric field and by introducing the highly electronegative chlorine into the reactor, the record growth rate of 11.5 µm h −1 is achieved and VG with a height of 100 µm is successfully synthesized. The theoretical study for the first time reveals that the introduction of chlorine accelerates the decomposition of methanol and thus promotes the VG growth in PECVD. Finally, as an excellent filler framework in polymer matrix, VG arrays are used to construct a free‐standing composite TIM, which yields a high vertical thermal conductivity of 34.2 W m −1 K −1 at the graphene loading of 8.6 wt% and shows excellent cooling effect in interfacial thermal dissipation of light emitting diode. Abstract : With a chloroform‐assisted method, a record growth rate of 11.5 µm h −1 was achieved and vertical graphene arrays with a height of 100 µm was successfully synthesized. Vertical graphene together with polydimethylsiloxane were used to construct a free‐standing thermal interface material, which yielded a high vertical thermal conductivity of 34.2 W m −1 K −1 and excellent cooling effect in light emitting diode.